Diagnostic accuracy of an automated microscope solution (miLab™) in detecting malaria parasites in symptomatic patients at point-of-care in Sudan: a case-control study - Hamid, Muzamil M. Abdel; Mohamed, Abdelrahim O.; Mohammed, Fayad O.; Elaagip, Arwa; Mustafa, Sayed A.; Elfaki, Tarig; Jebreel, Waleed M. A.; Albsheer, Musab M.; Dittrich, Sabine; Owusu, Ewurama D. A.; Yerlikaya, Seda (Malaria journal, 2024)
Microscopic detection of malaria parasites is labour-intensive, time-consuming, and expertise-demanding. Moreover, the slide interpretation is highly dependent on the staining technique and the technician’s expertise. Therefore, there is a growing interest in next-generation, fully- or semi-integrated microscopes that can improve slide preparation and examination. This study aimed to evaluate the clinical performance of miLab™ (Noul Inc., Republic of Korea), a fully-integrated automated microscopy device for the detection of malaria parasites in symptomatic patients at point-of-care in Sudan.